"Anishinaabe Time": Temporalities and Impact Assessment in Pipeline Reviews - Awasis, Sakihitowin (Journal of Political Ecology, 2020)
Indigenous ways of living that embrace multiple temporalities have been largely supplanted by a single, linear colonial temporality. Drawing on theoretical insights from Indigenous geographies and political ecology, this article considers how pipeline reviews come into being through contested temporalities and how dominant modes of time dispossess Indigenous peoples of self-determination in energy decision-making. In particular, Anishinaabe clan governance – a form of kinship that provides both social identity and function based on relations to animal nations – is undermined in colonial decision-making processes. Through analysis of documents from Canada’s National Energy Board and interviews with Anishinaabe pipeline opponents, I explore tensions between Anishinaabe and settler temporalities reflected in the 2012-17 Line 9 pipeline dispute in the Great Lakes region. These include divergent understandings of periodicities, timeframes, kinship relations, and the role of nonhuman temporalities in decision-making. Colonial temporal modes that have been imposed on Indigenous communities foreshorten timescales, depoliticize kinship relations, and discount nonhumans in decision-making – resulting in narrower and more short-sighted project reviews than Anishinaabe temporalities would support. I argue that the rich concepts of kinship, queerness, continuity, and prophecy embedded in Anishinaabe temporalities can inform strategies for decolonizing energy review processes and open possibilities for Indigenous self-determination in energy decision-making.